API day : design, build, integrate, and secure APIs in the API economy. (Live courses., 2023)
Sponsored by Rapid The API economy has precipitated a need for expert developers and architects who understand the intricacies of building, integrating, and monitoring APIs to connect distributed systems and deliver data for enhanced performance. API Day will give you a head start. Join host and API author Mike Amundsen and some of the top experts in software development to better understand the full picture of the API economy. You'll explore API options, service-oriented architectures, and security concerns; learn how to evolve existing legacy applications toward API-based systems and use API infrastructure for evolving or replatforming a system for effective cloud deployment; and so much more. Whether you're a business leader, security analyst, developer, or software architect, these practical sessions will help you build resilient applications as part of the API economy. What you'll learn and how you can apply it Learn how the API economy is driving and transforming distributed systems Understand how to design, build, integrate, and secure APIs Determine your API strategy for new software or legacy applications This live event is for you because... You're a software architect looking to evolve legacy systems using APIs and effectively integrate them without security risks. You're a software developer who needs strategies for successfully choosing and integrating APIs, as well as skills and tools for building robust and scalable APIs. You're part of an ops team dealing with the integration, governance, management, and automation of APIs and the applications using them. You're a security analyst who wants to better understand how to better combat the threat presented by recent increases in API attacks. You're a business leader looking to lead and accelerate your digital transformation efforts. Recommended follow-up: Read Mastering API Architecture (book) Read RESTful Web API Patterns and Practices Cookbook (book) Read Continuous API Management (book) Read Designing Web APIs: Building the APIs That Developers Love (book) Please note that slides or supplemental materials are not available for download from this recording. Resources are only provided at the time of the live event.